Consumer Perceptions of Foreign Brands and Cultural Identity in Uganda: The Moderating Role of Celebrity Endorsements - Walugembe, Ahmad; Kiggwe, Musa; Walusimbi, Yunus (Journal of Emerging Markets and Management, 2025)
This study investigates the moderating role of celebrity endorsement in the relationship between consumer perceptions of foreign brands and cultural identity within an emerging market context. Grounded in Social Identity Theory, the research adopts a positivist philosophical stance and uses a cross-sectional survey design, employing quantitative methods to explore how the perception of foreign brands influences cultural identity formation among consumers. The target population consisted of Ugandan consumers aged 20 to 60 years, a segment with purchasing power, brand awareness, and decision-making autonomy, with 405 respondents. Confirmatory Factor Analysis (CFA) was conducted using AMOS (v.26) to validate the measurement model. Pearson correlation results revealed a statistically significant positive relationship between consumer perception of foreign brands and cultural identity (r = 0.356, p < 0.01). Additionally, a significant relationship was found between Celebrity Endorsement and Consumer Perception of Foreign Brands (β = 0.656, CR = 11.924, p < 0.001). Further analysis with Structural Equation Modelling (SEM) confirmed that celebrity endorsement significantly moderates this relationship due to the indirect moderated path of Celebrity Endorsement, which is notably strong and significant (β = 0.62). This amplifies the symbolic and identity-shaping role of foreign brands’ perception. The findings show that foreign brands serve not only functional purposes but also act as tools for social identification, especially when endorsed by respected local figures. The study results imply that marketers in emerging markets move beyond traditional branding and strategically integrate celebrity endorsements and culturally resonant narratives to boost consumer engagement, brand relevance, and emotional connection with culturally diverse audiences.